694. The CAGE Study: Prevalence of Acute Gastroenteritis and Enteric Virus Infection in the Community. (26th November 2018) - Schmidt, Mark A; Salas, S Bianca; Yamshchikov, Vladimir; Groom, Holly; Rosales, Gabriela; Donald, Judy; Marsh, Zach; Burke, Rachel; Mattison, Claire; Naleway, Allison; Hall, Aron J
Abstract: Background: There are currently limited data about the occurrence and characteristics of sporadic acute gastroenteritis (AGE). In this study, we sought to (1) estimate the average point prevalence of AGE over a 1-year period; (2) describe health-seeking behaviors among those with AGE; and (3) calculate the proportion of stool samples testing positive for enteric viral pathogens. Methods: Starting in October 2016, we recruited 52 weekly, age-stratified, random samples of Kaiser Permanente Northwest members to complete an online survey and, for a subset of participants, to submit a stool specimen. The survey included questions about the occurrence of vomiting and/or diarrhea within the previous 30 days and, for those reporting AGE symptoms, related health-seeking behaviors. Collected stool samples were tested for norovirus, astrovirus, sapovirus, and rotavirus by RT-qPCR. Results: We received a total of 3, 483 surveys from eligible participants, 417 (12%) of whom reported having had AGE symptoms (Figure 1). Of these, 70 (17%) sought related medical care across a spectrum of clinical encounter types (Figure 2). We also received a total of 531 stool samples, 74 from symptomatic and 457 from asymptomatic individuals. Among them, we detected norovirus in 12% and 3% of samples ( P = 0.0005), respectively; astrovirus and sapovirus in 1% of samples in each group; and rotavirus in 8% and 7% of samples, respectively. Conclusion: Our findings of AGE within the community are consistent with previous estimates using models of medically attended AGE occurrence and reported rates of health-seeking behavior. The prevalence of enteric viral infection among people in the community without AGE was generally low. These data can be used to generate age-stratified incidence estimates of community AGE and specifically that associated with enteric viral pathogens. Such disease burden data are needed to guide the development, targeting, and anticipated impacts of interventions, such as vaccines. Disclosures: M. A. Schmidt, Takeda Vaccines, Inc.: Investigator, Research grant. S. B. Salas, Takeda Vaccines, Inc.: Investigator, Research grant. H. Groom, Takeda Vaccines, Inc.: Investigator, Research grant. G. Rosales, Takeda Vaccines, Inc.: Investigator, Research grant. J. Donald, Takeda Vaccines, Inc.: Investigator, Research grant. A. Naleway, Takeda Vaccines, Inc.: Investigator, Research grant.